Near-infrared fluorescence and nuclear imaging and targeting of prostate cancer - Wu, Jason (AME Publishing Company, 2013)
Despite advances in the treatment of castration-resistant and bone metastatic prostate cancer (PCa), there is still no clear demonstration that PCa growth and metastases can be unambiguously detected. We review recent advances including our own development of near-infrared fluorescence (NIRF) and near-infrared nuclear (NIRN) imaging approaches. We validated our results in experimental models of PCa bone and soft tissue metastases including PCa colonization at metastatic sites by injecting PCa cells either intratibially or intracardiacally. We describe our experience using noninvasive imaging and targeting modalities to probe PCa tumors grown at metastatic sites, molecular studies to understand the multiple molecular and cellular processes within tumor cells and their interactions with the tumor microenvironment, and targeting tumor growth at metastatic bone site. In this review, current knowledge and emerging technologies based on NIRF and NIRN disciplines will be summarized. Additionally the mechanisms of differential uptake of these agents by normal and cancerous cells will be described.